Treatment of Inactive Ovaries of Holstein Dairy Cows by Epidural Injection of GnRH Analogue (Receptal) and Its Impact on the Reproductive Hormones, Oxidant/Antioxidant Profile and Micro and Macro-Elements Profile - Yahia A. Amin; Alaa Eldin Z. Mahmoud; Rana A. Ali; Samer S. Fouad; Obeid Shanab; Rawia M. Ibrahim; Foad Farrag; Mustafa Shukry; Samah F. Ibrahim; Liana Fericean; Ragab Hassan Mohamed (Animals, 2023)
This study was designed to evaluate a new therapeutic approach for inactive ovaries based on the epidural administration of a GnRH agonist (Receptal) and an investigation of the impact of this treatment on the hormonal, oxidant/antioxidant and micro- and macro-element profiles. Sixty cows with postpartum anestrus were divided into two groups: the first group (group Repid, n = 30) was administered an epidural injection of Receptal, while the second group (group Cepid, n = 30) received saline and was considered the control group. Evaluation of hormonal (progesterone, FSH, LH, testosterone, and cortisol), oxidant/antioxidant (MDA, SOD, GPx and TAC) as well as micro- and macroelement (calcium, phosphorus, manganese and magnesium) profiles was done in serum. The results showed that the epidural injection of Receptal has the potential to induce estrus response and conception incidence in treated cows. Compared to the control group, progesterone, FSH, and LH concentrations were significantly increased in the treated group, whereas testosterone and cortisol decreased (p < 0.05) following treatment. In addition, the treated group had greater TAC and GPx concentrations than the control group. Serum concentrations of magnesium increased (p < 0.05) following receptal treatment, but differences in other minerals were not detected. This research suggests a novel, effective method of treating inactive ovaries with epidural infusion of a GnRH agonist.